(untitled) - Kotter, John P. (Boston, 2012)
From the ill-fated dot-com bubble to unprecedented M&A activity to scandal, greed, and, ultimately, recession -- we've learned that widespread and difficult change is no longer the exception. It's the rule. The author's eight-step process for managing change with positive results has become the foundation for leaders and organizations across the globe. By outlining the process organizations have used to achieve transformational goals and by identifying where and how even top performers derail during the change process, the author provides a practical resource for leaders and managers charged with making change initiatives work.
Keywords: Thay đổi tổ chức,Khả năng lãnh đạo,Organizational change,Leadership